Assessment of urethral support using MRI-derived computational modeling of the female pelvis. Issue 2 (February 2016) - Peng, Yun; Khavari, Rose; Nakib, Nissrine; Boone, Timothy; Zhang, Yingchun
Abstract Introduction and hypothesis This study aimed to assess the role of individual anatomical structures and their combinations to urethral support function. Methods A realistic pelvic model was developed from an asymptomatic female patient's magnetic resonance (MR) images for dynamic biomechanical analysis using the finite element method. Validation was performed by comparing simulation results with dynamic MR imaging observations. Weaknesses of anatomical support structures were simulated by reducing their material stiffness. Urethral mobility was quantified by examining urethral axis excursion from rest to the final state (intra-abdominal pressure = 100 cmH2 O). Seven individual support structures and five of their combinations were studied. Result Among seven urethral support structures, we found that weakening the vaginal walls, puborectalis muscle, and pubococcygeus muscle generated the top three largest urethral excursion angles. A linear relationship was found between urethral axis excursions and intra-abdominal pressure. Weakening all three levator ani components together caused a larger weakening effect than the sum of each individually weakened component, indicating a nonlinearly additive pattern. The pelvic floor responded to different weakening conditions distinctly: weakening the vaginal wall developed urethral mobility through the collapsed vaginal canal, while weakening the levator ani showed a more uniform pelvic floor deformation. Conclusions The computational modeling and dynamic biomechanical analysis provides a powerful tool to better understand the dynamics of the female pelvis under pressure events. The vaginal walls, puborectalis, and pubococcygeus are the most important individual structures in providing urethral support. The levator ani muscle group provides urethral support in a well-coordinated way with a nonlinearly additive pattern.